Kesetaraan Hak Antara Karyawan Laki-Laki Dan Perempuan Di Kebun Binatang Bandung - Irgi Yudha Prawira; Rini Sulastri (Gunung Djati Conference Series, 2024)
In the development of the tourism industry, men and women have their own roles according to their own capacity when building local tourism. This research focuses on the Bandung Zoo, which is a favorite recreational and educational tourist destination for residents of Bandung and its surroundings. The purpose of the research is to find out the equality of male and female employees within the scope of the tourism industry to achieve their justice. The author also finds out about the manager's management in fulfilling the rights of its employees in every aspect. The author uses a qualitative approach as the method used. In the data collection process, the author uses interview techniques in the data collection process. The data collected is processed into a descriptive narrative about the equal rights of male and female employees at the Bandung Zoo. In the results of the study, the manager, namely the Tamansari Wildlife Foundation, was able to be fair to all employees, both men and women. The employees are given the same opportunity to work which is proven by competence. Then, the manager can be fair in all aspects of the work.